2015
DOI: 10.1128/jvi.03545-14
|View full text |Cite
|
Sign up to set email alerts
|

The Interface between Hepatitis B Virus Capsid Proteins Affects Self-Assembly, Pregenomic RNA Packaging, and Reverse Transcription

Abstract: Hepatitis B virus (HBV) capsid proteins (Cps) assemble around the pregenomic RNA (pgRNA) and viral reverse transcriptase (P). pgRNA is then reverse transcribed to double-stranded DNA (dsDNA) within the capsid. The Cp assembly domain, which forms the shell of the capsid, regulates assembly kinetics and capsid stability. The Cp, via its nucleic acid-binding C-terminal domain, also affects nucleic acid organization. We hypothesize that the structure of the capsid may also have a direct effect on nucleic acid proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
101
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 61 publications
(107 reference statements)
2
101
0
Order By: Relevance
“…A very recent report showed that mutations at another NTD site, V124, at the core-dimer interface (Fig. 7), close to I126, also led to a selective defect in mature RC DNA accumulation, although the defects of those mutants were attributed to RC DNA synthesis rather than destabilization (25). It is important to point out that the precise quantification of the synthesis versus degradation of the different DNA species was difficult, due to the dynamic nature of NC maturation and degradation, NC uncoating, RC DNA deproteination, and conversion to CCC DNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A very recent report showed that mutations at another NTD site, V124, at the core-dimer interface (Fig. 7), close to I126, also led to a selective defect in mature RC DNA accumulation, although the defects of those mutants were attributed to RC DNA synthesis rather than destabilization (25). It is important to point out that the precise quantification of the synthesis versus degradation of the different DNA species was difficult, due to the dynamic nature of NC maturation and degradation, NC uncoating, RC DNA deproteination, and conversion to CCC DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the I126, together with that of the nearby V124 at the dimer interface (25) (Fig. 7), in mature NC formation/ integrity suggests that maturation-associated NC structural changes, perhaps triggered by the altered interactions of HBc with the dsDNA in mature NCs versus the ssDNA or pgRNA in immature NCs (52), may be initiated and/or propagated through the dimer interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Residue V124 of core protein forms part of the wall of the HAP pocket. Replacing V124 with amino acid residues with a hydrophobic side chain of different size partially fills the HAP pocket and alters capsid assembly and interaction with capsid assembly modulators (43,44). Specifically, the V124A mutation (Fig.…”
mentioning
confidence: 99%
“…Reverse transcription (RT) occurs within capsids. Cp is an active participant in genome replication, synthesizing first the minus-strand DNA and subsequently the dsDNA from the pgRNA template (12)(13)(14)(15). Three distinct template switches occur during genome replication, among which the second template switch determines if the major form of relaxed circular (RC) or the minor form of duplex linear (DL) dsDNA is synthesized (16).…”
mentioning
confidence: 99%